Pengaruh Kualitas Pelayanan terhadap Kepuasan Pengunjung: Studi pada Wisata Kuliner TPI Ikan Bakar Kelapa Lima - Rizal, Moehammad As’adhur; Fanggidae, Rolland E.; Neno, Marianus S. (Jurnal Studi Perhotelan dan Pariwisata, 2022)
Purpose: This research was conducted at TPI Ikan Bakar Kelapa Lima in the Kelapa Lima District, Kupang City. The main problem addressed in this study is to determine whether there is a positive and significant effect of service quality on visitor satisfaction. Methodology: The study treats service quality as an independent variable and visitor satisfaction as the dependent variable. The population for this study consisted of at least 5 visitors who decided to make a purchase, and since there are 84 stalls at TPI Ikan Bakar Kelapa Lima, the total number of visitors who decided to make a purchase every day is 420. The sample for this study was selected using the accidental sampling technique, resulting in 81 respondents. The data collected was analyzed using simple linear regression analysis, which included a simple linear test, hypothesis testing through a t-test, descriptive statistical analysis, and analysis of the coefficient of determination (R2) Results: Based on the research results, the following simple linear regression equation was obtained: Y = 0.552 + 0.800X. The hypothesis testing using the t-test revealed that the service quality variable has a significant effect on visitor satisfaction. The service quality variable obtained a t-value of 4.865 with a significance level of 0.000. The t-table value was 1.668 (df = 79, calculated by subtracting 2 from 81). Since the significance value of 0.000 is smaller than the alpha value of 0.05 (? < ?) and the t-value is greater than the t-table value (4.865 > 1.664), we can conclude that the service quality variable has a significant effect on visitor satisfaction. The Adjusted R-squared value, which represents the coefficient of determination (R2), is 0.688 or 68.00%. This indicates that the Service Quality variable (X) influences the Visitor Satisfaction variable (Y) by 68.00%, while the remaining 32.00% is influenced by other variables not discussed in this study. Limitations: The limitations of this study include the respondents experiencing relocation and the trading place undergoing relocation as well, resulting in them only recently returning to the new trading place and not yet experiencing the benefits of the renovated trading place. Therefore, further research is needed to study the conditions of the new trading place. Contribution: (1). Based on the descriptive analysis of the Service Quality and Visitor Satisfaction variables, they fall into the category of excellent. This means that there is a positive assessment and a favorable impression in the customers' minds. (2). The hypothesis testing results were obtained using regression analysis. The null hypothesis (Ho), which states that there is no relationship between service quality and visitor satisfaction, can be rejected. The testing results indicate that there is a significant influence between service quality and visitor satisfaction at TPI Ikan Bakar Kelapa Lima. It can be concluded that the Visitor Satisfaction variable has a strong influence on the Service Quality variable at TPI Ikan Bakar Kelapa Lima.